Vision-Based Bridge Deformation Monitoring - Brownjohn, James Mark William; Xu, Yan; Hester, David (Frontiers in Built Environment, 2017)
Optics-based tracking of civil structures is not new, due to historical application in surveying, but automated applications capable of tracking at rates that capture dynamic effects are now a hot research topic in structural health monitoring. Recent innovations show promise of true non-contacting monitoring capability avoiding the need for physically attached sensor arrays. The paper reviews recent experience using the Imetrum Dynamic Station (DMS) commercial optics-based tracking system on Humber Bridge and Tamar Bridge, aiming to show both the potential and limitations. In particular the paper focuses on the challenges to field application of such a system resulting from camera instability, nature of the target (artificial or structural feature) and illumination. The paper ends with evaluation of a non-proprietary system using a consumer grade camera for cable vibration monitoring to emphasise the potential for lower cost systems where if performance specifications can be relaxed.